Berdampingan dengan Leluhur di Masa Depan: Historisitas, Lanskap, dan Artikulasi Identitas Masyarakat Tengger Senduro - Rohmah, Nabilla Nailur (Masyarakat Indonesia, 2020)
Abstract This article studies the historical significances of the ancestral tenet and the landscape of Puncak Songolikur for Tengger people in Senduro and howÂ  they are being performed, represented, and reconstructed in the present historical context. In this paper, the Folklore of Tengger about â€œJoko Seger and Roro Antengâ€ is studied neither as legend nor myth, but as public history which has relevances to the present social realities. For them, the story of the origin of their ancestor encompasses the overall theological framework that underlies the social order and cultural practices in their everyday life. The five religions policy during authoritarianÂ  New Order regime has led to a massive Hinduization and Islamization which has great influence on social and cultural order of Tengger people. Moreover,Â  the enforcement of national park and tourism policy in their living space has raised greater challenge which manifests an increasingly capitalistic and profane life order. Under this condition, Puncak Songolikur presents and preserves the historical narrative about their ancestor as well as spiritual values, social order, cultural practice, and all the way of life. However, the development of tourist destination â€œPuncak B29â€ in the landscape of Puncak Songolikur since 2013 has become both challenge and opportunity for their historical narratives. This paper explores how tourism developent maintains and simultaneously contests the historicity of Puncak Songolikur. It includes how people assert, negotiate, and rearticulate their identity in nowadays cosmopolite historical horizon.